Performance of invasive, non-invasive, and pharmacological measures by emergency physicians in the German emergency medical services. A retrospective cross-sectional study from the rescue association Südwestsachsen - Koch, Sebastian; Suffeda, Michelle (Frontiers in Disaster and Emergency Medicine, 2023)
Background: Every citizen in Germany is entitled to qualified emergency medical assistance.Due to annually increasing deployment figures and personnel shortages, it is no longer possible to guarantee 24/7 coverage of all emergency physician locations throughout Germany. Relief can be achieved through changes in the supply structures. Professional field analyses are the basis for the further development of training and care structures. Methodology: All emergency physician deployments of a location in the rescue association Südwestsachsen that took place between 01.10.2022 and 31.01.2023 were retrospectively evaluated. For this purpose, the analogously created deployment protocols were examined with regard to demographic data as well as the invasive, non-invasive and pharmacological measures performed by emergency physicians. Results: In N = 684 emergency missions, n = 471 (100%) invasive or noninvasive measures were performed by an emergency physician. At n = 383 (81.3%), the most frequently performed invasive measure was intravenous (i.v.) access. There were n = 710 (100%) pharmacological measures performed by an emergency physician. The most frequently performed pharmacologic measure was administration of a full electrolyte solution, with n = 223 (31.4%) Discussion: Emergency physician interventions do not necessarily involve invasive, noninvasive, or pharmacologic measures. The emergency paramedic learns a variety of invasive, noninvasive, and pharmacologic measures in his or her training and could contribute to the reduction of emergency physician interventions. An adaptation of prehospital care structures based on evidence-based data and an update of the catalog of indications for emergency physician interventions would be elementary for this goal.